EFEKTIVITAS FUNGSI PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH TERHADAP KEBIJAKAN LAHAN PEMAKAMAN PERUMAHAN DI KABUPATEN KARAWANG - Altas, Aldo; Labolo, Muhadam; Sinaga, Jona Bungaran Basuki (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The focus of this research is to describe the effectiveness of the Regional People's Representative Council's supervision of the residential cemetery land policy in Karawang Regency and determine the strategy that should be carried out by the Regional People's Representative Council in carrying out supervision of the residential cemetery land policy in Karawang Regency. This research uses Sutrisno's theory of program effectiveness which consists of the following dimensions: a. Understanding of the program; b. Right on target; c. Right on time; d. Achievement of goals; e. Changes to the program. Achievement of goals; e. Real changes. This research uses descriptive qualitative methods. In collecting data, researchers conducted interviews, documentation, observation and data triangulation on the effectiveness of the supervisory function of the Regional People's Representative Council on residential cemetery land in Karawang Regency. The results showed that from several dimensions, namely understanding the program, on target, on time, and real changes were good, while the dimension of achieving goals was still in the insufficient category. Using SWOT analysis and litmus test, it was found that the strategies that should be carried out by the Regional People's Representative Council in carrying out supervision of housing burial land policies in Karawang Regency area. allocating an operational budget to increase human resources and supporting technology for policy supervision, b. cooperating with stakeholder support for DPRD partners in developing standard operating procedures (SOPs) for policy supervision, c. conducting socialization related to housing PSUs to increase public understanding, d. optimizing the function of the website as a means of public complaints.Keywords: Effectiveness, Policy Supervision, DPRD